PERBANDINGAN PENERAPAN MOOCs DAN WHATSAPP MENGGUNAKAN MODEL PROJECT-BASED LEARNING PADA MATA KULIAH KIMIA ORGANIK 1 TERHADAP HASIL BELAJAR MAHASISWA - Dewi Handayani; Elvinawati; Uliyandari, Mellyta (University of Bengkulu, 2025)
This study aims to improve the quality of learning in Organic Chemistry 1. The specific objective of this study is to determine the difference in learning outcomes between students who use MOOCs (Massive Open Online Courses) and WhatsApp using the Project-Based Learning model. The type of research used is quasi-experimental research with a sample of third-semester students from Class A and Class B. This study uses two experimental classes, namely Class A using MOOCs and Class B using the WhatsApp application. The data analysis used is the average score, homogeneity test, normality test, and t-test. Based on the research results, there is a difference in learning outcomes between MOOCs and WhatsApp Group (WAG) applications with the same learning model treatment, namely the PjBL model, with a sig value (2-tailed) of 0.000, indicating p < 0.05. It can be concluded that there is a significant difference in the learning outcomes of the two experimental classes. Student responses to MOOCs and WAG applications are very good. Students stated that MOOCs and WAG applications are very practical, interesting, and easily accessible, especially for access to learning materials. Keywords: MOOCs, WhatsApp, Learning Outcomes, Project-based learning